28.7k views
5 votes
-7x+12-2x=23+13x simplify by combining like terms that are on the same side of the equation

User Poly Bug
by
5.9k points

2 Answers

2 votes

Answer:

Answer in picture

Explanation:

-7x+12-2x=23+13x simplify by combining like terms that are on the same side of the-example-1
User Pumba
by
5.5k points
6 votes

Answer:

Explanation:

Let's move all terms to the left side of the equation.

First, combine the x terms. To do this, subtract 13x from both sides, obtaining:

-7x - 13x - 2x = 23. Proceeding further, we get -22x = 23, or -22x - 23 = 0, or

22x + 23 = 0.

User Flavaflo
by
5.8k points